2010
DOI: 10.1369/jhc.2010.955773
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde Dehydrogenase 3B1 (ALDH3B1): Immunohistochemical Tissue Distribution and Cellular-specific Localization in Normal and Cancerous Human Tissues

Abstract: S U M M A R Y Aldehyde dehydrogenase (ALDH) enzymes are critical in the detoxification of endogenous and exogenous aldehydes. Our previous findings indicate that the ALDH3B1 enzyme is expressed in several mouse tissues and is catalytically active toward aldehydes derived from lipid peroxidation, suggesting a potential role against oxidative stress. The aim of this study was to elucidate by immunohistochemistry the tissue, cellular, and subcellular distribution of ALDH3B1 in normal human tissues and in tumors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 87 publications
0
21
0
Order By: Relevance
“…ALDH3B1 is expressed in the kidney, liver, and brain and has been shown active in vitro toward C6 to C9 aldehydes [12]; however, its activity toward ≥C10 aldehydes is currently unknown. In addition, although ALDH3B1 is suggested to be localized in the plasma membrane and cytosol [13,14], the precise intracellular localization still remains to be elucidated. Unlike other ALDH3 family members, ALDH3B2 has so far not been well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…ALDH3B1 is expressed in the kidney, liver, and brain and has been shown active in vitro toward C6 to C9 aldehydes [12]; however, its activity toward ≥C10 aldehydes is currently unknown. In addition, although ALDH3B1 is suggested to be localized in the plasma membrane and cytosol [13,14], the precise intracellular localization still remains to be elucidated. Unlike other ALDH3 family members, ALDH3B2 has so far not been well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, among the most significant genes for lung tumor, the following were found in C2 genesets related to lung and not in those related to breast: ALDH3B1, DARS, PRPSAP2, FAM96B, MBIP, LRRC20. The overexpression of ALDH3B1 in lung tumors has been reported in [49]. Santarius et al [50] gives lists of genes, the overexpression of which is associated to different types of human cancers.…”
Section: Resultsmentioning
confidence: 99%
“…A recent meta-analysis showed that increased ALDH1A1 expression is associated with poor OS and disease-free survival in lung cancer patients [35]. Previous studies showed that also several other ALDH isoforms are involved in lung cancer as ALDH3A1, highly expressed in two types of NSCLC, Ade and SCC, and ALDH3B1 expression was also found to be upregulated in a high percentage of human tumors, particularly in lung cancer [36][37][38].…”
Section: Aldh Family Proteinsmentioning
confidence: 99%